1987
DOI: 10.1007/bf01422668
|View full text |Cite
|
Sign up to set email alerts
|

On the determination of micellar aggregation numbers from the concentration dependence of13C NMR chemical shifts

Abstract: Abstract:The assumptions underlying the extraction of micellar aggregation numbers by means of applying the mass action law to the concentration dependence of i3C Nuclear Magnetic Resonance (NMR) shift data are discussed. Such data are presented for sodium dodecylsulfate and it is shown that the extracted aggregation numbers are far too small. It is argued that this is in part due to a failure of the mass action law to describe the micellization process but also due to covariance in the parameters of the mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…The resulting N (Table ) are small, ranging from 4 to 6 molecules per aggregate, for all SCGEs, and N for C 4 E 3 is close to the literature value . Although NMR studies have been shown to underestimate the aggregation numbers of surfactants, NMR studies tend to agree well with aggregation numbers determined from other methods (e.g., conductivity and light scattering) for small aggregates …”
Section: Resultssupporting
confidence: 76%
“…The resulting N (Table ) are small, ranging from 4 to 6 molecules per aggregate, for all SCGEs, and N for C 4 E 3 is close to the literature value . Although NMR studies have been shown to underestimate the aggregation numbers of surfactants, NMR studies tend to agree well with aggregation numbers determined from other methods (e.g., conductivity and light scattering) for small aggregates …”
Section: Resultssupporting
confidence: 76%
“…There is a shift difference between free and micellized amphiphile, and since the observed shifts are weighted averages of these two environments, the shifts will change as the fraction of free monomers decreases with increase of total concentration. In general, aggregation numbers obtained from NMR measurements tend to be lower than those obtained using other techniques (30,31). Nevertheless, in this study the values in Table 3 support the conclusions from light scattering and those of the earlier study (9) of limited self-association of this drug.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 98%
“…In fact, for ionic surfactants C f decreases after the cmc (see below). Secondly, in the fitting procedure there is marked covariance between the constant terms involving the standard chemical potentials and the aggregation number, such that neither can be determined with a reasonable degree of accuracy (24). Finally, we note that the phase separation model is obtained by setting N ϭ ϱ in Eq.…”
Section: The Determination Of Cmcmentioning
confidence: 99%